2010
DOI: 10.2169/internalmedicine.49.4088
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Chronic Hepatitis C May be More Sensitive to Iron Hepatotoxicity than Patients with HFE-Hemochromatosis

Abstract: Aim In chronic hepatitis C, iron might play an important role as a hepatotoxic co-factor. Therefore, venesection, a standard treatment for hemochromatosis, has been proposed as an alternative for patients who respond poorly to anti-viral therapy. To improve our understanding of iron-induced hepatotoxicity, we compared the responses to venesection between patients with chronic hepatitis C and those with HFEhemochromatosis. Methods Fourteen Japanese patients with chronic hepatitis C and eight Italian patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…This process is thought to contribute to hepatocellular necrosis and/or apoptosis in the liver with the subsequent activation of hepatic stellate cells and development of hepatic fibrosis and cirrhosis 26 . Similar to the hepatitis virus, iron may induce fibrosis via hepatocellular necrosis 27 . The patient with the HAMP genotype examined in this study first presented with hepatitis at 26 years of age 19 .…”
Section: Discussionmentioning
confidence: 97%
“…This process is thought to contribute to hepatocellular necrosis and/or apoptosis in the liver with the subsequent activation of hepatic stellate cells and development of hepatic fibrosis and cirrhosis 26 . Similar to the hepatitis virus, iron may induce fibrosis via hepatocellular necrosis 27 . The patient with the HAMP genotype examined in this study first presented with hepatitis at 26 years of age 19 .…”
Section: Discussionmentioning
confidence: 97%
“…As most subjects had normal HIC at baseline, we feel it is unlikely that the improvement in liver histology is solely due to reduction in liver iron. It is quite possible that iron reduction has anti‐inflammatory effects independent from decreasing tissue iron . Iron is a known potent catalyst of oxidative stress and may play a role in inducing fibrogenesis …”
Section: Discussionmentioning
confidence: 99%
“…In fact phlebotomy was an accepted therapy for hepatitis C infection in the United States and Japan before the advent of directacting antiviral agents. [16][17][18] In a systematic review, Fanchini et al reported that patients treated with phlebotomy followed by interferon therapy (in 7 studies with 373 patients) had an odds ratio of 2.32 (95% CI: 0.96-6.24) for achieving a sustained virologic response as compared to patients receiving interferon alone 19 ; of note, in that metaanalysis CIs crossed 1, thus weakening the demonstration. Similarly, in a second meta-analysis of 6 randomized controlled trials including 367 patients, Desai and co-workers compared interferon therapy alone to interferon plus concomitant phlebotomy.…”
Section: Deleterious Effects Of Liver Iron Deposits On the Natural Himentioning
confidence: 94%
“…In addition, phlebotomy improves histologic lesions and potentiates the salutary effects of interferon. In fact phlebotomy was an accepted therapy for hepatitis C infection in the United States and Japan before the advent of direct‐acting antiviral agents . In a systematic review, Fanchini et al reported that patients treated with phlebotomy followed by interferon therapy (in 7 studies with 373 patients) had an odds ratio of 2.32 (95% CI: 0.96–6.24) for achieving a sustained virologic response as compared to patients receiving interferon alone; of note, in that meta‐analysis CIs crossed 1, thus weakening the demonstration.…”
Section: Deleterious Effects Of Liver Iron Deposits On the Natural Himentioning
confidence: 96%